A Framework for Formal Verification of Behavior Trees With Linear Temporal Logic - Biggar, Oliver; Zamani, Mohammad (IEEE robotics and automation letters, 2020)
Despite the current increasing popularity of Behavior Trees (BTs) in the robotics community, there does not currently exist a method to formally verify their correctness without compromising their most valuable traits: modularity, flexibility and reusability. In this letter we present a new mathematical framework in which we formally express Behavior Trees in Linear Temporal Logic (LTL). We show how this framework equivalently represents classical BTs. Then we utilize the proposed framework to construct an algorithm to verify that a given BT satisfies a given LTL specification. We prove that this algorithm is sound. Importantly, we prove that this method does not compromise the flexible design process of BTs, i.e. changes to subtrees can be verified separately and their combination can be assured to be correct. We present an example of the proposed algorithm in use.